Stability of Urine Glucose in Active-Smoking Adolescents with Delayed Examination Times - Widiyanti, Ni Made Risa; Dwi Putri, Ni Luh Nova Dilisca; Ayu, Ni Ketut; Mirayanti, Mirayanti (Jurnal Laboratorium Khatulistiwa, 2025)
Urine glucose is one of the important parameters in early screening for glucose metabolism disorders. The presence of glucose in urine occurs when blood glucose levels exceed the renal threshold, causing it to be excreted in the urine. Adolescents with long-term smoking habits may develop insulin resistance, which increases the risk of glucosuria. This study aimed to describe the results of urine glucose examinations among active-smoking adolescents with delayed testing at 2, 4, and 6 hours at a storage temperature of 2–8°C in Private College X. This research employed a descriptive observational design. The samples consisted of 30 active-smoking adolescents whose urine specimens were examined using the dipstick method. The results showed that all urine samples were negative for glucose, even after a delay of up to 6 hours. No indicator color changes were observed on the test strips during the storage period. These findings may be related to stable glucose metabolism and an intact renal reabsorption threshold in adolescents.